Lived experiences of maternal near misses: a qualitative study in the Kilimanjaro Region, Tanzania - Enna G. Sengoka; Gunilla Björling; Michael J. Mahande; Janet Mattsson; Gileard Masenga (Reproductive Health)
Abstract Background In recent years, Tanzania has significantly reduced maternal mortality rates; however, pregnant women in Tanzania still face severe health risks and complications. The rate of maternal near misses is nearly 60% higher in Tanzania compared to other low-income countries. Women who survive severe complications during pregnancy or childbirth may experience long-lasting adverse effects, such as poor physical health, impaired sexual function, psychological distress, and a decreased quality of life. Therefore, our research aimed to understand the lived experiences of Tanzanian women who survived severe maternal complications within their cultural and social context. Method By using the Sub-Saharan Africa criteria for near misses, twelve (12) women who survived severe maternal complications were recruited between August and September 2022. The study utilized a descriptive qualitative design with an inductive approach to explore women's lived experiences of a maternal near miss. The participants were purposively sampled and interviewed face-to-face in the hospital or their homes six weeks after discharge from the hospital. Recorded interviews were transcribed and analysed using Graneheim and Lundman's content analysis. Results The analysis revealed four themes and eight subthemes. The themes were living with severe maternal complications, impact on social life, perception of obstetric care services and person-centred care. The informants described pain experiences, weakness, fear, financial difficulties, neglect, long waiting times, and a lack of information. However, they also mentioned a need for increased awareness of danger signs, care satisfaction, and the importance of close relatives' social support. Conclusion Maternal near misses have a great impact on women's physical, financial, and mental well-being. Women also experience long service waiting times, communication barriers, and neglect. Good healthcare, person-centred care, patient education, and psychological support can improve women’s lived experiences.